Accomplishments, Status, and Road Map for the US Department of Energy's Fossil Energy SOFC Program. (2nd June 2015) - White, Briggs M.; Lundberg, Wayne L.; Pierre, Joseph F.
Abstract : The U.S. Department of Energy Office of Fossil Energy is charged with developing ultraclean (near-zero emissions), low-cost energy from fossil fuels to fuel economic prosperity, strengthen energy independence, and enhance environmental quality. A component of that effort, implemented by the National Energy Technology Laboratory, is the Solid State Energy Conversion Alliance, which is developing low-cost, highly efficient solid oxide fuel cell power systems that produce electric power from natural gas or coal with intrinsic carbon capture capabilities. In coordinated work involving industry, academia, and national laboratories, progress is being made in areas critical to technology commercialization, including seals, cells power density and stability, and low-cost interconnects. Cell tests have yielded acceptable performance and degradation rates. The program is now focusing on improving stack and system performance, reliability, and durability through progressively larger stack tests and integrated systems tests. Accomplishments, current program status, and the roadmap for continuing work are reviewed.